Catalisadores NiMoS suportados em sílicas mesoporosas ordenadas para a hidrodessulfurização de organossulfurados refratários: efeito do ácido oxálico como agente quelante e avaliação de fases ativas - Albuquerque, Jonas Santana (Universidade Federal de São Carlos, 2024)
In the last decades, regulatory agencies have been establishing stricter specifications for fuels in relation to the emission of pollutants and, especially, the sulfur content. Therefore, hydrodesulfurization (HDS) is an essential step in oil refining for the production of fuels with a low content of organosulfur compounds, respecting the specifications proposed by current legislation. Conventional catalysts are based on metal sulphides of NiMo supported on alumina, however, due to its low hydrogenating capacity and strong metal-support interaction, HDS of refractory organosulfur becomes limited. Seeking to minimize these limitations, the objective of this work was the study of catalysts, supported on mesostructured silicas, with subsequent evaluation in the HDS reaction of dibenzothiophene and 4,6-dimethyldibenzothiophene. Different methodologies for the synthesis of mesostructured supports (SBA-15, SBA-16 and Al-SBA-15) and the influence of using oxalic acid as a chelating agent on the impregnation of the nickel precursor were evaluated in this sudy. Results show that mesostructured supports with optimized textural properties and moderate Brønsted acidity play an important role in obtaining highly active catalysts for HDS of refractory compounds. The use of oxalic acid generated nickel oxalate complexes with low interaction with molybdenum, increasing the dispersion and formation of the MoS2 active phase, especially in catalysts supported on Al-SBA-15. All oxide precursors with oxalic acid, (Ni-AO)Mo, showed reduction peaks at lower temperatures and hexacoordinated molybdate species with octahedral geometry (Mo (Oh)). The NiMoS/Al-15 and (Ni-AO)MoS/Al-15 catalysts presented the highest DBT conversions, while the NiMoS/15 catalyst was considered the most promising for the HDS of 4,6-DMDBT, as it presented the highest hydrogenating capacity, better dispersion of the active phase and total conversion of the organosulfur compound into desulfurized hydrocarbons. Finally, the (Ni-AO)MoS/Al-15 catalyst achieved conversions above 90% at the end of the 8 h reaction of the third reuse cycle, showing that no apparent deactivation occurs.
NiMoS catalysts supported on ordered mesoporous silicas for the hydrodesulfurization of refractory organosulfur compounds: effect of oxalic acid as a chelating agent and evaluation of active phases
Keywords: Catalisadores NiMoS; Sílicas mesoestruturadas; Ácido oxálico; Hidrodessulfurização; ENGENHARIAS::ENGENHARIA QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA; 7. Energia limpa e acessível; 9. Indústria, Inovação e Infraestrutura